PENGARUH KEPATUHAN WAJIB PAJAK DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PPH PASAL 25/29 WAJIB PAJAK BADAN PADA KPP PRATAMA DENPASAR TIMUR - RATNA SARI, MARIA M.; AFRIYANTI, NI NYOMAN (Jurnal Ilmiah Akuntansi dan Bisnis, 2012)
The purpose of this research is to examine the impact of taxpayer compliance and tax audit on company income tax revenue 25/29 at Taxation Office KPP Pratama Denpasar Timur for the period of 2004 to 2008. Population consists of active taxpayer during the period. Data are collected using several methods, including interview, documentation, and nonbehavioral observation. Regression model used has met the classical assumptions. Data are analyzed using multiple linear regressions. Based on analysis, it could be concluded that taxpayer compliance and tax audit simultaneously and partially affect company income tax revenue 25/29 significantly, and the dominant factor is tax audit.
Keywords: tax compliance, tax audit, company taxpayer